A study of the frequency dependence of conductivity of silicon whiskers at cryogenic temperatures as basis for the temperature sensors - A. A. Дружинин; И. П. Островский; Ю. Н. Ховерко; Р. Н. Корецкий (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
Studies of low-temperature features of semiconductor silicon whisker conductivity play a significant role in the development of electronic devices, such as temperature sensors. The results of studies of the active component of impedance Z' for silicon whiskers obtained at cryogenic temperatures, indicating the increase of its value under temperature decreasing, and showing the frequency dependence in the range from 0 to 250 kHz. It was found that in temperature range 4.2–20 K at a frequency ωкр which can amount from 8 to 20 kHz, depending on resistivity and temperature, the hopping conduction with the participation of phonons is observed in whisker samples, resulting in a significant reduction of Z' value at frequencies up to 250 kHz. For example, at a temperature of 4.2 K for the sample with resistivity ρ300K=0.0168 Ohm • cm the frequency ωкр is equal to 8 kHz, and in frequency range up to 250 kHz the active component of impedance is reduced approximately by half. Such behavior of the frequency response for these samples is kept up to 20 K, whereas at 25 K the value of Z' is almost independent of frequency, and at higher temperatures with the increasing of frequency, it slightly increases. Reducing the resistivity of the samples leads to a narrowing of the temperature range, where the hopping conduction is observed, and at ρ300K= 0.0143 Ohm•cm it is observed only at a helium temperature. Offset of the frequency ωкр from 8 to 20 kHz at the hopping conduction beginning, depending on temperature and the value of resistivity for studied silicon crystals, can be attributed to the change of free charge carriers concentration in such samples, because it determines the effect of Coulomb gap on ωкр. Experimental study of low-temperature conductivity of silicon whiskers allowed proposing the temperature sensor operable at temperature range 4.2–100 K. The sensor works on alternating current, because it avoids the sell-heating of sensitive element and the occurrence of «parasitic» thermopower, which also affects the accuracy of temperature measurement.